2018
DOI: 10.1111/sji.12718
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant IL‐35 levels in patients with primary Sjogren's syndrome

Abstract: Objective IL‐35 is a newly discovered immunoregulatory cytokine that possesses the ability to inhibit CD4 + effector T cells and alleviate autoimmune diseases. The objective of this study was to investigate IL‐35 levels in patients with primary Sjogren's syndrome (pSS) and explore the roles of IL‐35 in the pathogenesis of pSS. Methods Thirty‐four hospitalized patients with pSS were recruited, and 34 volunteers were enrolled as healthy controls. An ELISA was adopted to measure plasma IL‐35 levels. The levels of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…We showed an elevation of plasma IL- 35 Recent studies have revealed abnormal expression of IL-35 in inflammatory autoimmune diseases, and suggested the critical regulatory role in the onset and development of these diseases [21,22]. Decreased expression of peripheral IL-35 was reported in patients with systemic lupus erythematosus [23], multiple sclerosis [24], primary Sjogren's syndrome [25], and psoriasis vulgaris [26]. In contrast, intestinal regulatory B cells and circulating regulatory CD4 + /CD8 + T cells produced high level of IL-35 in active inflammatory bowel disease [27].…”
Section: Discussionmentioning
confidence: 69%
“…We showed an elevation of plasma IL- 35 Recent studies have revealed abnormal expression of IL-35 in inflammatory autoimmune diseases, and suggested the critical regulatory role in the onset and development of these diseases [21,22]. Decreased expression of peripheral IL-35 was reported in patients with systemic lupus erythematosus [23], multiple sclerosis [24], primary Sjogren's syndrome [25], and psoriasis vulgaris [26]. In contrast, intestinal regulatory B cells and circulating regulatory CD4 + /CD8 + T cells produced high level of IL-35 in active inflammatory bowel disease [27].…”
Section: Discussionmentioning
confidence: 69%
“…There were no remarkable differences of either FasL or TRAIL mRNA level between cell with and without IL-35 stimulation (paired t tests, p>0.05, Figure 3g and 3h). Decreased expression of peripheral IL-35 was reported in patients with systemic lupus erythematosus [24], multiple sclerosis [25], primary Sjogren's syndrome [26], and psoriasis vulgaris [27]. In contrast, intestinal regulatory B cells and circulating regulatory CD4 + /CD8 + T cells produced high level of IL-35 in active inflammatory bowel disease [28].…”
Section: In Vitro Il-35 Stimulation Suppressed Cd14 + Monocytes Mediamentioning
confidence: 99%
“…Decreased expression of peripheral IL-35 was reported in patients with systemic lupus erythematosus [24], multiple sclerosis [25], primary Sjogren's syndrome [26], and psoriasis vulgaris [27]. In contrast, intestinal regulatory B cells and circulating regulatory CD4 + /CD8 + T cells produced high level of IL-35 in active inflammatory bowel disease [28].…”
Section: Recent Studies Have Revealed Abnormal Expression Of Il-35 Inmentioning
confidence: 99%